Fictions of land and flesh : blackness, indigeneity, speculation - Rifkin, Mark, 1974- (Duke University Press, 2019)
Mark Rifkin turns to black and indigenous speculative fiction to show how it offers a site to better understand black and indigenous political movements' differing orientations in ways that can foster forms of mutual engagement and cooperation without subsuming them into a single political framework in the name of solidarity.